The Role of Islamic Microfinance For Poverty Alleviation in Bandung, Indonesia - Febianto, Irawan; Johari, Fuadah Binti; @Zulkefli, Zurina Binti Kefeli (Universitas Ahmad Dahlan, 2019)
The emergence of Islamic micro financial institution becomes the alternative solution for the micro-entrepreneurs who need working capital assistance. However, the impact of Islamic microfinance institution in reducing poverty level is somewhat still debatable. In Indonesia, Islamic microfinance established through the presence of Baitul Mal wa Tamwil (BMT), the most popular type of Islamic microfinance institutions. BMT providing financing for the micro-entrepreneurs, as their potential clients, that operates their activities mostly at the traditional markets. The purpose of this study is to measure the impact of BMT for poverty alleviation in Bandung as the capital city of West Java as the biggest population province in Indonesia, not only based on material level but also on spiritual level. This study is looking at income variables of micro-entrepreneur’s household, as well as the spiritual level indicator of micro-entrepreneur before and after they received financing from BMT. The primary data obtained through in-depth questionnaires in Bandung, Indonesia.